The role of spirituality in feelings of suffering and quality of life in self-introduced addicts - Ali Akbar Pirasteh Motlagh; Zahra Nikmanesh; Ehsan Liaghat; Mojahed Hematian (Gonabad University of Medical Sciences, 2019)
Many researches are seeking evidence and ways in which spirituality can improve the feeling of suffering and quality of life in drug abuse addicts. This study was aimed to investigate the role of spirituality in feelings of suffering and quality of life in self-introduced addicts referring to addiction treatment centers. The statistical population consisted all of self-introduced addicts referring to addiction treatment centers in Yasuj city. 120 participants were selected by convenience sampling. Following instruments were used for data collection; spirituality questionnaire, scale of experience and perception of suffering and the world health organization quality of life questionnaire. The results showed that there was a significant negative correlation between spirituality and feelings of suffering. There was a significant positive correlation between spirituality and quality of life. Stepwise regression results showed that the best predictors of spiritual/existential suffering were self- awareness and spiritual activities. Also, the component of self-awareness was the best predictor of physical health, psychological health, environmental health and quality of life and social relations. Therefore, reinforcement of spirituality in addicts and encouraging them to perform the related activities can reduce the feeling of pain among them and improve their quality of lives.